2006
DOI: 10.1021/jp062095i
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Spectroscopy of Small Neutral Silver Clusters

Abstract: The vibrational spectra of Ag(3) and Ag(4) are recorded in the far-infrared between 100 and 220 cm(-1) using multiple photon dissociation spectroscopy of their complexes with Ar atoms. For Ag(3)-Ar two IR active bands are found at 113 and 183 cm(-1), for Ag(4)-Ar one band at 163 cm(-1) and very weak IR activity at 193 cm(-1) are observed. This, together with recent theoretical studies, allows for a reassignment of the controversial vibrational data reported earlier for the bare Ag(3) cluster. The influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 56 publications
6
33
0
2
Order By: Relevance
“…Starting initially with cationic clusters of Group 5 metals (V, Nb, Ta), [43,44] these studies have since then been extended to cationic clusters of late transition metals which are relevant in heterogeneous catalysis [42,45,46] and also to neutral clusters. [44,[47][48][49] For certain clusters it has even been possible to obtain isomer-specific IR spectra by making use of the differences in their ionization potentials, that is, by selective ionization of the cluster/rare gas complex of a single isomer near the threshold. [49] H.-J.Freund, G. Meijer, M. Scheffler, R. Schlçgl, M. Wolf…”
Section: Structural Characterization Of Transition-metal Clustersmentioning
confidence: 99%
“…Starting initially with cationic clusters of Group 5 metals (V, Nb, Ta), [43,44] these studies have since then been extended to cationic clusters of late transition metals which are relevant in heterogeneous catalysis [42,45,46] and also to neutral clusters. [44,[47][48][49] For certain clusters it has even been possible to obtain isomer-specific IR spectra by making use of the differences in their ionization potentials, that is, by selective ionization of the cluster/rare gas complex of a single isomer near the threshold. [49] H.-J.Freund, G. Meijer, M. Scheffler, R. Schlçgl, M. Wolf…”
Section: Structural Characterization Of Transition-metal Clustersmentioning
confidence: 99%
“…16 These investigations have so far been limited to V + n (n = 3 − 23) 15,17 , Nb 0/+ n (n = 5 − 9) 16,18,19 as well as to Ag 3 and Ag 4 . 20 Here we present the vibrational spectra of cationic tantalum clusters Ta + n , containing 6 to 20 atoms, and round off our investigations on clusters of the metals from group 5 of the periodic system, that in the bulk all have the same body centered cubic (bcc) structure. From this complete study one can learn about structural similarities and differences for a certain cluster size within one group.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even for some paramagnetic MLSC species postulated from the absorption and the PL spectra like Ag 2 þ or Ag 3 2þ , ESR signals were not observed in some situations. 19 Fortunately, it is shown that far-IR spectra 28,29 and powder XRD 30 (Ag 3 2þ ), here we tentatively assign the 460 nm and the $560 nm emissions to Ag 3 2þ trimers. Efforts on determining the exact species of the SCs by employing some useful tools, such as high resolution XRD and quantum chemistry modulation, 31,32 are going to be made in our future work.…”
Section: Resultsmentioning
confidence: 52%